Mediating role of emotion regulation in the relationship between parental attachment and smartphone addiction among adolescents - Kalender, Bilal; Şen Demirdöğen, Ezgi; Bahadır, Erdi (Journal of Dependence, 2023)
Objective: This study aimed to examine the effect of parental attachment on smartphone addiction and the mediating role of emotion regulation in adolescents aged 15-18 years. Method: Relational survey model, one of the quantitative research methods, was used in the study. The sample of the study consisted of 380 high school students, 175 of whom were female and 205 of whom were male, between the ages of 15-18. Demographic data form, Smartphone Addiction Scale, Difficulty in Emotion Regulation Scale-Short Form and Parental Attachment Scale-Short Form were used as data collection tools. Results: Low-level, negative and significant relationships were observed between smartphone addiction and maternal attachment and paternal attachment scores. Similarly, low-level, negatively significant relationships were found between difficulties in emotion regulation and maternal attachment and paternal attachment scores. The full mediating role of emotion dysregulation in the prediction of maternal attachment to smartphone addiction was statistically significant. Attachment to mother and emotion regulation explained 15% of the variance of smartphone addiction. In addition, the partial mediating role of emotion dysregulation in the prediction of attachment to father was found to be statistically significant. Attachment to father and emotion regulation explained 15% of the variance of smartphone addiction. Conclusion: Parents have different levels of roles in preventive and protective steps towards smartphone addiction. In addition, studies or trainings to be conducted by experts on emotion regulation difficulties may be useful as a preventive step in the development of smartphone addiction.